2017
DOI: 10.1080/09603123.2017.1339782
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between emergency care utilization, ambient temperature, and the pollution standard index in Taiwan

Abstract: This study applied a vector error correction model to investigate the effects of ambient temperature (AT) and air quality index values on emergency care utilization (ECU). The Pollution Standards Index (PSI) and total suspended particulates (TSP) were used for analysis. Data were obtained from the National Health Insurance Research Database of the Ministry of Transportation and Communications and Ministry Environmental of Protection Administration of Taiwan. Data from January of 1998 to December of 2012 (180 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…Significant increases in mortality and emergency hospital admissions were observed during heat waves, mainly affecting the elderly and people with cardiovascular, renal, or diabetic diseases [ 29 ]. Specific monitoring of ambient temperatures and of total suspended particulates by the Ministry of Transportation would therefore help to respond to the increased frequency of high-risk patients consulting EDs [ 65 ]. Emergency medical structures should implement the WHO-proposed strategy for managing health crises and put in place policies for the prevention and management of risks [ 66 ].…”
Section: The Mitigation Strategies Of Ed Managersmentioning
confidence: 99%
“…Significant increases in mortality and emergency hospital admissions were observed during heat waves, mainly affecting the elderly and people with cardiovascular, renal, or diabetic diseases [ 29 ]. Specific monitoring of ambient temperatures and of total suspended particulates by the Ministry of Transportation would therefore help to respond to the increased frequency of high-risk patients consulting EDs [ 65 ]. Emergency medical structures should implement the WHO-proposed strategy for managing health crises and put in place policies for the prevention and management of risks [ 66 ].…”
Section: The Mitigation Strategies Of Ed Managersmentioning
confidence: 99%
“…In doing so, we were specifically interested in examining air pollution effects by considering their toxico- [20] [21]. To support our findings, one study reported long-term exposure of air pollutants measured with API did not show significant predictor to emergency admissions [22]. Despite the study measured different health outcomes, we believed the use of a single weighted parameter by combining various air pollutants incapacitates to predict the chronic health effects that associated with ambient air exposure.…”
Section: Discussionmentioning
confidence: 67%